Cytokinins: Their Impact on Molecular and Growth Responses to Drought Stress and Recovery in Arabidopsis - Prerostova, Sylva; Dobrev, Petre I.; Gaudinova, Alena; Knirsch, Vojtech; Körber, Niklas; Pieruschka, Roland; Fiorani, Fabio; Brzobohatý, Břetislav; černý, Martin; Spichal, Lukas; Humplik, Jan; Vanek, Tomas; et al. (Frontiers in Plant Science, 2018)
Our phenotyping and hormonal study has characterized the role of cytokinins (CK) in the drought and recovery responses of Arabidopsis thaliana. CK down-regulation was achieved by overexpression of the gene for CK deactivating enzyme cytokinin oxidase/dehydrogenase (CKX): constitutive (35S:CKX) or at the stress onset using a dexamethasone-inducible pOp/LhGR promoter (DEX:CKX). The 35S:CKX plants exhibited slow ontogenesis and higher expression levels of stress-associated genes, e.g., AtP5CS1, already at well-watered conditions. CK down-regulation resulted during drought in higher stress tolerance (indicated by relatively low up-regulation of the expression of drought stress marker gene AtRD29B) accompanied with lower leaf water loss. Nevertheless, these plants exhibited slow and delayed recovery after re-watering. CK levels were increased at the stress onset by stimulation of the expression of CK biosynthetic gene isopentenyl transferase (ipt) (DEX:IPT) or by application of exogenous CK meta-topolin. After water withdrawal, long-term CK elevation resulted in higher water loss in comparison with CKX transformants as well as with plants overexpressing ipt driven by senescence-inducible SAG12 promoter (SAG:IPT), which gradually enhanced CKs during the stress progression. In all cases, CK up-regulation resulted in fast and more vigorous recovery. All drought-stressed plants exhibited growth suppression associated with elevation of abscisic acid and decrease of auxins and active CKs (with the exception of SAG:IPT plants). Apart from the ipt overexpressers, also increase of jasmonic and salicylic acid was found.